PENDIDIKAN ISLAM RASULULLAH SAW PERIODE MADINAH: STRATEGI, MATERI DAN LEMBAGA PENDIDIKAN - Mahfud Ifendi (STAI Sangatta Kutai Timur, 2021)
What Rasulullah SAW did during the Medina period was a continuous effort from what he had previously taught while still in Mecca. However, all the policies and strategies carried out by the Prophet in Medina are a development and a step forward to form a civil society that is faithful, polite, clever, tolerant, upholds differences, and has extensive knowledge. Through a qualitative descriptive approach, this article describes the strategy, materials and educational institutions of the Prophet in the Medina period through scientific articles and reference books. Building mosques, resolving conflicts and establishing the state of Medina were the strategies carried out by the Prophet Muhammad in Medina to build a new civilization and power under the banner of Islam. And by being taught some educational material in the form of monotheism, al-Qur'an, economics, social, politics, and brotherhood. And the emergence of several Islamic educational institutions in the form of mosques, suffah and kuttab, have become evidence that what the Prophet Muhammad did was an effort to make humans more civilized and knowledgeable compared to previous times, when Islam had not yet arrived in the Arabian peninsula.